Analysis of the Results of the Reduction of Cyanide Acid Content in Hevea brasiliensis Seeds - Diah Ayu Kusuma Putri; Sulhadi Sulhadi; Teguh Darsono (Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2019)
Rubber seeds (Hevea brasiliensis) are part of rubber plants that have not been utilized optimaly. The content contained in rubber seeds is sufficient, including fat content of 68.53 g/100 g, proteins 17.41 g/100 g, and carbohydratees 6.99 g/100 g. However, the obstacle faced is the presence of toxic compounds found in rubber seeds namely cyanide acid (HCN) which is very dangerous if it enters the body. The purpose of this study is to find out the right treatment to reduce the content of cyanide acid so that the rubber seeds can be utilized. The research method uses experimental comparative. The variation used in the reduction process is to soak the rubber seeds respectively for 12, 24, and 36 hours by replacing the immersion water once every 2 hours, then boil the rubber seeds into 2 liters of water for 2 hours by replacing the boiled water for 1 hour. The results showed that the greatest decrease in cyanide acid content occurred during soaking for 36 hours with boiling for 2 hours.©2019 JNSMR UIN Walisongo. All rights reserved.